Vital Stains in Retina and Vitreous - Shreyangshi Dipta; Shruti Bhattacharya; Khushboo Chawla (Delhi Journal of Ophthalmology)
Dyes used to stain living tissues are known as vital dyes and these have become an effective surgical aid in ocular tissue identification and visualization in ophthalmology. “Chromovitrectomy” is a phrase used for describing the use of vital dyes to stain these transparent tissues and facilitate their manipulation during vitreo-retinal surgery.1 Common vital dyes used in the posterior segment are indocyanine green (ICG) and brilliant blue (BB); and dyes which are still under research include patent blue, bromophenol blue, light green, and Evans's blue.